Analysis of Investor Psychology and Investment Decision - Tika Prasad Sapkota (Journal of Business and Social Sciences, 2025)
The study aims to examine on how investors decisions are influenced by psychological factors on the Nepalese stock exchange. The study uses descriptive and causal-comparative research methodologies to address problems related to the influences of economic and psychological factors in investors' decision making on the Nepalese stock exchange. The 150 Nepalese stock exchange investors from Ward No. 5 of Hetauda sub-metropolitan City who are currently making investments make up the study's sample. One hundred and fifty questionnaires are gathered in order to analyze individual investment decision-making. The primary sources of data used in this study were questionnaires with a 5-point Likert scale that were given to NEPSE investors. Individual investor decision-making is the dependent variable, whereas profitability, risk-taking ability, and price movement information effect are the independent variables. Risk-taking ability and price movement information are found to be significantly correlated with individual investors' decision-making. These factors show positive coefficients, suggesting that investors are more inclined to make decisions when they have greater risk-taking capacity and access to price movement information. However, profitability is not statistically significant with individual investors' decision-making. As a result, investors with a higher risk tolerance actively take price movement information into account and exhibit overconfidence while making investment decisions. It is crucial to remember that these conclusions are predicated on the examined data and a particular sample. When making investing selections, investors should take into account a variety of aspects, including their personal risk tolerance, market conditions, and financial objectives.